A mathematical model of receptive field reorganization following stroke - Einarsdottir, Hildur (2007)
Insufficient blood transport to neurons in the brain due to blocked or ruptured blood vessels (stroke) can lead to damage or death of cells, causing functional impairment. Intact neurons surrounding a stroke-like lesion have been shown to adapt to the damage by expanding their sensory receptive fields in the direction towards the lesion, thereby restoring information processing capacity within the cortex. We developed model of the effect of focal ischaemia on the performance of a neuronal population code, in order to study physiological parameters that could be influenced to enhance recovery from stroke. Our findings show that recovery of the accuracy of the population code is optimal by a specific amount of receptive field plasticity. This plasticity may be influenced by changing the level of gamma-aminobutyric acid (GABA-ergic) inhibition in the areas surrounding the damaged tissue.